Do Intratumoral And Peritumoral Apparent Diffusion Coefficient (ADC) Values Have A Role In The Diagnosis Of Pediatric Brain Tumors? - Güleç Mert Doğan; Ahmet Sığırcı; Sevgi Taşolar; Aslınur Cengiz; Hilal Er Ulubaba; Selami Çagatay Önal; Neşe Karadağ (Galenos Publishing House, 2020)
INTRODUCTION: The motion of water particles within biological tissues, which is called random Brownian motion, is detected at the microscopic level by Diffusion-Weighted Imaging (DWI) sequence of Magnetic Resonance Image technique. The Apparent Diffusion Coefficient (ADC) calculated on DWI has been used for tumor diagnosis and grading. The purpose of this study was to evaluate of ADC values in the differential diagnosis of supratentorial and infratentorial pediatric brain tumors and to reveal the difference of peritumoral ADC measurements of pediatric patients from adult patients. METHODS: All of the 56 pediatric patients included in this retrospective study had lesions >1 cm in diameter on magnetic resonance image and all of the diagnosies were confirmed by histopathology. Intratumoral and peritumoral ADC values and ratios were measured in diffusion weighted Magnetic Resonance Image. RESULTS: The 58.9% (n=33) of these tumors were supratentorial and 41.1% (n=23) were infratentorial. ADC values and ADC ratios were significantly lower in high-grade tumors than low-grade tumors (p<0.05). Peritumoral ADC values in high-grade tumors were lower than low grade tumors (p<0.05). The cut-off value of the ADC ratio between these two groups was 1 and the ADC cut-off value was 1.1*10-3 mm2/s. DISCUSSION AND CONCLUSION: In the differentiation of low and high-grade pediatric brain tumors, cut-off values of 1.1*10_3mm2/s for ADC Value and 1.0 for ADC Ratio may be useful. Although, peritumoral ADC values differ in children compared to the adult group, both intratumoral and peritumoral ADC values can help for grading pediatric brain tumors.